Infoenergy: Technology for Replacing Massive Degradation with Speedier (Cleaner) Energy - Ferran, Carlos; Salim, Ricardo (International Journal of Energy Economics and Policy, 2013)
This paper provides an information technology perspective of energy that can help explain and promote more environmentally friendly energy sources. Following the equation energy equals mass times velocity squared (E = m * v2), a source 10 times more massive will produce 10 times more energy, but a source 10 times faster will produce 100 times more energy. Since chemical sources such as oil combustion are about ten times faster than mechanical sources such as waterfalls and winds, getting the same quantity of energy out of wind would require 10 times more mass (steel and concrete for wind towers), than getting it out of burning oil (CO2 and oil plants materials). A nuclear source is one million times faster than chemical, thus its mass requirement is negligible but technology (mainly information technology) is needed to safely drive its speed allowing us to substitute mass -i.e. future debris- with information. Keywords: energy, environment, information technology, nuclear, quadratic contribution, energy technology, clean energy, matter minimization JEL Classifications: H00; O10; O33; Q29; Q39; Q42; Q43; Q48